RP-HPLC Analytical Method Development and Validation for Simultaneous Estimation of Three Drugs: Glimepiride, Pioglitazone, and Metformin and Its Pharmaceutical Dosage Forms - Gadapa Nirupa; Upendra M. Tripathi (Journal of Chemistry)
Developing a single analytical method for estimation of individual drug from a multidrug composition is a very challenging task. A simple, rapid, precise, and reliable reverse phase HPLC method was developed for the separation and estimation of three drugs glimepiride, pioglitazone and metformin in bulk drug mix and pharmaceutical dosage forms. The estimation was carried out using Inertsil ODS-3V (250 mm × 4.6 mm, 5 μm) column; mobile phase consisting of acetonitrile, tetrahydrofuran, and buffer at pH 5; the flow rate of 1.7 mL/min and ultraviolet detection at 228 nm. All the three drugs were properly resolved having run time of 5 minutes, 3.9 minutes and 1.3 minutes for glimepiride, pioglitazone, and metformin, respectively. The method was validated as a final verification of method development with respect to precision, linearity, accuracy, ruggedness, and robustness. The validated method was successfully applied to the commercially available pharmaceutical dosage form, yielding very good and reproducible result.